A Study of Academic Achievement in Mathematics of 7th Class Students of Sirsa District: Examining Factors Affecting Academic Achievement in Mathematics of 7th Class Students (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In this paper the academic achievement of 7th class students BSEH students were taken as research problem. This study has been conducted on 200 students of 7th class of Sirsa district. These students have been further categorized into Government and Private school students and further classified on the basis of sex and area. In this study Mathematics Achievement Test authored by Ali Imam and Tahira Khatoon was used. The data was collected with the help of standardized Mathematics Achievement Test and Mean, S.D and‘t’ test was applied for analysis and interpretation of data. In this study the Private school students was having better Academic achievement in Mathematics as compare to Government school students. Similarly the male and urban area Private and Government school students were having better academic achievement in Mathematics than female and rural area Private and Government school students. The results indicates that the academic achievement in Mathematics in Private schools is found better than Governments schools because the facilities in private schools was given better than Governments schools academically. Similarly the urban area male students were having better results in mathematics due to more resources given to them. The Government schools and schools situated in rural areas and females should be given more resources financially, academically so that improvement in government schools, rural area schools and in females may be acquired.